Antioxidant Responses and Phytochemical Accumulation in Raphanus Species Sprouts through Elicitors and Predictive Models under High Temperature Stress - María-Trinidad Toro; Roberto Fustos-Toribio; Jaime Ortiz; José Becerra; Nelson Zapata; María Dolores López-Belchí (MDPI AG, 2024)
Crop production is being impacted by higher temperatures, which can decrease food yield and pose a threat to human nutrition. In the current study, edible and wild radish sprouts were exposed to elevated growth temperatures along with the exogenous application of various elicitors to activate defense mechanisms. Developmental traits, oxidative damage, glucosinolate and anthocyanin content, and antioxidant capacity were evaluated alongside the development of a predictive model. A combination of four elicitors (citric acid, methyl jasmonate-MeJa, chitosan, and K2SO4) and high temperatures were applied. The accumulation of bioactives was significantly enhanced through the application of two elicitors, K2SO4 and methyl jasmonate (MeJa). The combination of high temperature with MeJa prominently activated oxidative mechanisms. Consequently, an artificial neural network was developed to predict the behavior of MeJa and temperature, providing a valuable projection of plant growth responses. This study demonstrates that the use of elicitors and predictive analytics serves as an effective tool to investigate responses and enhance the nutritional value of Raphanus species sprouts under future conditions of increased temperature.